Design of Automatic Parking System of Lhokseumawe State Polytechnic Using RFID - Amri, .; Muhammad, Rizka; Mulyadi, .; Akmalul, Fata; Ilham, Safar (INTI International University, 2024)
The design of the barrier or portal system now in use predominantly relies on a manual mechanism; however, the automatic barrier door of the Lhokseumawe State Polytechnic aims to create a device that facilitates the opening and closing of the parking portal for users. This Portal system employs RFID (Radio Frequency identifying) cards as identifying tags for vehicles entering and exiting. This autonomous portal comprises several components, specifically an RFID (Radio Frequency Identification) Tag, an RFID Reader, a Servo Motor, an Arduino Uno, and a Buzzer. The servo motor is designed to elevate and lower the barrier door, while the buzzer is intended to detect vehicles entering and exiting via unregistered RFID (Radio Frequency Identification) tags.